Bibliometric Analysis of Palm Oil Competitiveness Study in Indonesia and The Linkage to Agricultural Trade - Bahtera, Novyandra Ilham; Novianti, Tanti; Septiyanti, Ratih (Jambura Agribusiness Journal, 2025)
The global palm oil industry has become a focal point in agricultural trade due to its economic significance and environmental implications. As one of the world’s largest producers, Indonesia faces increasing pressure to maintain its competitiveness while addressing sustainability and trade policy challenges. This study aims to assess the development of scientific literature on Indonesian palm oil competitiveness and its relationship with global agricultural trade dynamics. The study was conducted using bibliometric analysis of 648 scientific articles obtained from Google Scholar and Scopus using the keyword "palm oil competitiveness". The articles were published in the time span from 1992 to 2025 for documents sourced from Google Scholar and the time span from 1985 to 2025 for documents sourced from Scopus.The data was analysed using Bibliometrix (R) and VOSviewer software to identify publication trends, main keywords, and interconnections between topics in the literature. The results showed a significant increase in the number of publications in the last decade, signalling high attention to the issue of palm oil competitiveness. Keywords such as “competitiveness”, “export performance”, “market share”, and “sustainable development” were central in the literature network, illustrating the important role of economic, policy, and sustainability aspects in strengthening Indonesia's palm oil position in the global market. The findings showed that palm oil competitiveness did not only depend on production efficiency, but also required downstream policy support, capacity building of farmers, and strengthening of trade diplomacy. This research was expected to serve as a reference for academics and policymakers in formulating a sustainable, equitable palm oil development strategy that was able to adaptively respond to global trade challenges.